Immediate results of surgical treatment of peripheral hepatic cholangiocarcinoma in elderly and senile patients - O. Yu. Usenko; O. V. Hrynenko; A. І. Zhylenko; O. O. Popov; A. V. Husiev (Клінічна хірургія, 2020)
Objective. To estimate immediate results of surgical treatment of peripheral cholangiocarcinoma in elderly and senile patients.